Reading and Writing with Eyes and Ears toward the Other - Moyers, Tony (The international journal of religion and spirituality in society, 2021)
Reading is from the beginning, before any analysis, an ethical act; at the outset, the reader stands obligated. Responsibility begins with an author, which makes historical readings obligated to do more than just analyze biblical texts. Texts with ethical implications need further consideration. Readers and reading communities are responsible for how their readings affect the lives of others, especially the marginalized. Such assessments require more than a historical description of an author’s intention or a doubling commentary on a text. Scrutiny of how a biblical author or text affects the lives of others needs to be part of any ethical interpretation. Readers should listen for faint voices and look for the trace of the Other inhabiting biblical texts.